Proceedings of the 2017 ACM SIGCSE Technical Symposium on Computer Science Education 2017
DOI: 10.1145/3017680.3017769
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Children's Understanding of the Work of Computer Scientists

Abstract: We developed the Draw-A-Computer-Scientist-Test (DACST) to better understand elementary school students' conceptions of computer scientists and the nature of their work. By understanding how young children perceive computer scientists, we can broaden their ideas about the activities and images of computer scientists. We administered the DACST to 87 fourth-grade students (ages 8-9) as a pre-and post-assessment to a computer science curriculum. All students attended the same school and were taught by the same fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 24 publications
0
30
1
Order By: Relevance
“…Some of the stereotypes that hold girls back in STEM are acquired as early as first grade. For instance, Cvencek, Meltzoff, and Greenwald (2011) reported that children in the first and second grades already associate mathematics with boys and reading with girls, differences which tend to persist over time (Nagy et al, 2010) Similarly, elementaryschool girls typically draw a man when asked to draw a computer scientist (Hansen et al, 2017) or a mathematician (though they are more likely to draw a girl when the prompt is "child mathematician"; Steele, 2003). Reflecting women's increasing representation in scientific fields (e.g., Miller & Wai, 2015), the likelihood of young girls drawing men as scientists has dropped in recent years, though they are still more likely to draw a male than a female scientist by the end of elementary school (Miller, Nolla, Eagly, & Uttal, 2018).…”
Section: Early Acquisitionmentioning
confidence: 99%
“…Some of the stereotypes that hold girls back in STEM are acquired as early as first grade. For instance, Cvencek, Meltzoff, and Greenwald (2011) reported that children in the first and second grades already associate mathematics with boys and reading with girls, differences which tend to persist over time (Nagy et al, 2010) Similarly, elementaryschool girls typically draw a man when asked to draw a computer scientist (Hansen et al, 2017) or a mathematician (though they are more likely to draw a girl when the prompt is "child mathematician"; Steele, 2003). Reflecting women's increasing representation in scientific fields (e.g., Miller & Wai, 2015), the likelihood of young girls drawing men as scientists has dropped in recent years, though they are still more likely to draw a male than a female scientist by the end of elementary school (Miller, Nolla, Eagly, & Uttal, 2018).…”
Section: Early Acquisitionmentioning
confidence: 99%
“…Classroom environments are one way that students experience the computing discipline. The experiences students have with computing, even from an early age, and the process of acquiring the foundational knowledge of the field shapes the way they think about computing and their computing identity (Hansen et al, 2017;Schulte & Knobelsdork, 2007;Zander, Boustedt, McCartney, Mostrom, Sanders & Thomas, 2009;Wong, 2016).…”
Section: Sense Of Belongingmentioning
confidence: 99%
“…In a similar fashion, the impact of the prompt has been noted and utilized for alternative research foci, like conceptions related to scientists in different fields of science (e.g. Hansen et al, 2017;Oktay & Eryurt, 2012).…”
Section: The Stereotypic Image and The Modified Dastmentioning
confidence: 99%